Leaching of Copper Secondary Wastes: Possible Soil Contaminants - Hussain, Zaib; Grimes, Sue; Shahid, Muhammad; Anwer Bukhari, Shazia; Ali Raza Naqvi, Syed; Pirzada, Tajnees; Zia, Sobia (Asian Journal of Chemistry, 2013)
The United Nations Basel convention on the transboundary shipment of hazardous wastes was adopted to control the influx of hazardous materials being shipped from OECD countries to non-OECD countries. The ban allowed for developing countries to control the level of pollution and contamination prevailing in soils, water and the atmosphere. This study aims to look at the hazards posed by the secondary wastes industries, focusing in particular on copper slags, drosses and residues. To establish the levels of heavy metals becoming available in the environment, these wastes were extracted in different leach liquors. The results indicated that copper residue is more drastic toward soil and water contaminations. High amount of Cu from three different samples were leached, 39431.9, 7402.6 and 119301.6 μg/L, under physiological soil pH condition. Other heavy metals Pb and Zn were also calculated in concentration 10.1, 139.57 and 29.48 μg/L respectively. A significant improvement in morphology was also recorded from the scanning electron microscopic analysis.